Data integrity of small laboratory instruments integrated to laboratory information management system - Eerola, Lotta (My University, 2025)
The digital transformation of the pharmaceutical industry has raised the importance of data integrity in laboratory operations. Ensuring data integrity is vital for pharmaceutical safety and efficacy, especially as laboratories adopt digital tools. This research examined the role of a Laboratory Information Management System (LIMS) in improving data integrity for small laboratory instruments. The focus was on how LIMS enhanced data integrity, mitigated risks, and supported compliance with regulations and industry guidelines. The research involved analysing the current data integrity compliance of selected instruments and evaluating their integration into the LIMS. Data for the analysis was collected through instrument-specific evaluations, user requirement specifications, and data integrity risk assessments. Both independent standalone instruments and computer-operated instruments were analysed to understand the effects of LIMS integration on the security and traceability of laboratory data. LIMS integration addressed multiple data integrity challenges by improving user access and time control, audit trails, electronic signatures, data retention, and review processes. By reducing reliance on manual data handling and hybrid systems, LIMS integration significantly improved data integrity and enabled a seamless electronic data flow. Nevertheless, challenges remained, particularly in maintaining the linkage between raw and processed data, indicating areas for further enhancement. In conclusion, LIMS integration enhanced data integrity by automating processes, reducing manual interventions, and strengthening compliance with regulatory requirements. Future integrations should leverage modern instruments, advanced LIMS features, and explore emerging technologies like blockchain to further enhance data integrity in pharmaceutical laboratories.

Lääketeollisuuden digitalisoituminen on nostanut tiedon eheyden keskeiseksi tekijäksi laboratoriotoiminnassa. Tiedon eheyden varmistaminen on olennainen edellytys lääkkeiden turvallisuuden ja tehon takaamiseksi, erityisesti laboratorioiden siirtyessä digitaalisiin työkaluihin. Tässä työssä tarkasteltiin, kuinka laboratorion tiedonhallintajärjestelmä (LIMS) voi parantaa tiedon eheyttä pienlaboratoriolaitteiden osalta. Tutkimuksessa keskityttiin siihen, miten LIMS-järjestelmä vahvistaa tiedon eheyttä, vähentää riskejä sekä tukee sääntelyn ja alan ohjeistusten noudattamista. Tutkimuksessa analysoitiin valittujen laitteiden nykyistä tiedon eheyden tasoa ja arvioitiin niiden integrointia LIMS-järjestelmään. Aineistona hyödynnettiin laitekohtaisia arviointeja, käyttäjävaatimuksia ja tiedon eheyden riskiarvioita. Tarkasteluun sisällytettiin sekä itsenäiset pienlaitteet että tietokoneohjatut laitteet, jotta LIMS-integraation vaikutuksia laboratoriotiedon turvallisuuteen ja jäljitettävyyteen voitiin arvioida kattavasti. LIMS-integraatio auttoi ratkaisemaan useita tiedon eheyteen liittyviä haasteita parantamalla käyttäjä- ja ajanhallintaa, audit trail -toimintoja, sähköisiä allekirjoituksia, tiedon säilytystä ja tarkistusprosesseja. Manuaalisen tiedonkäsittelyn ja hybridijärjestelmien tarpeen väheneminen lisäsi tiedon eheyttä merkittävästi ja mahdollisti sujuvan sähköisen tiedonkulun. Erityiseksi haasteeksi nousi kuitenkin raakadatan ja prosessoidun tiedon välisen yhteyden säilyttäminen, mikä osoittaa kehitystarpeita jatkossa. Yhteenvetona voidaan todeta, että LIMS-integraatio paransi tiedon eheyttä automatisoimalla prosesseja, vähentämällä manuaalisia työvaiheita ja vahvistamalla säädösten noudattamista. Tulevissa laiteintegraatioissa olisi suositeltavaa hyödyntää moderneja laitteita, kehittyneitä LIMS-ominaisuuksia sekä lisäksi tutkia uusia teknologioita, kuten lohkoketjuja, jotta laboratoriotiedon eheys vahvistuisi edelleen.
Keywords: data integrity, digitalization, GxP, laboratory information management system, pharmaceutical industry